The Relationship of Patient Safety Culture to Compliance with the Implementation of Standard Precautions by Nurses in the Inpatition of Royal Prima Hospital Medan - Margaretia Yenni Rotua; Irza Haicha Pratama; Chrismis Novalinda Ginting (Jurnal Penelitian Pendidikan IPA, 2023)
Patient safety is a system that makes patient care safer, including risk assessment, identification and management of patient risks, incident reporting and analysis, the ability to learn from incidents and follow up, as well as implementing solutions to minimize risks and prevent injuries caused by errors. The consequences of carrying out an action or not taking an action that should be taken. This type of research is quantitative research with an analytical descriptive design. The level of compliance with the application of universal precautions shows that the majority of respondents are compliant in implementing universal precautions with a total of 73 respondents (58.4%) and for respondents whose level of Compliance with the Implementation of Universal Precautions is not 52 people (41.6%).